2017
DOI: 10.5606/archrheumatol.2017.5886
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio and Mean Platelet Volume as Inflammatory Indicators in Systemic Lupus Erythematosus Nephritis

Abstract: Objectives: This study aims to evaluate the role of neutrophil to lymphocyte ratio (NLR) and mean platelet volume (MPV) as activation and inflammatory markers in systemic lupus erythematosus (SLE) patients with nephritis. Patients and methods: A total of 108 SLE patients (8 males, 100 females; mean age 35.3±10.2 years; range 16 to 64 years) including 78 patients with renal involvement (8 males, 70 females; mean age 33.9±10.6 years; range 16 to 64 years) (SLEn+ group) and 30 patients without renal involvement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
10
1
4
Order By: Relevance
“…Higher MPV levels were reported in patients with renal involvement compared to patients without renal involvement. There have been statistically differences between both groups (23). There was a negative correlation between MPV and disease activity in SLE patients with renal involvement in our study.…”
Section: Discussioncontrasting
confidence: 39%
“…Higher MPV levels were reported in patients with renal involvement compared to patients without renal involvement. There have been statistically differences between both groups (23). There was a negative correlation between MPV and disease activity in SLE patients with renal involvement in our study.…”
Section: Discussioncontrasting
confidence: 39%
“…During the full-text review process, four studies were further excluded for lacking the data of interest. Finally, 14 studies with 1,781 SLE patients and 1,330 healthy controls were included in this meta-analysis (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Study Selectionmentioning
confidence: 99%
“…The synthesized result showed that an increased NLR was closely associated with active SLE (SMD=2.05; 95% CI, 0.87-3.23) ( Figure 3). Additionally, four studies of 441 patients explored the difference in NLR between SLE patients with versus without lupus nephritis (22,23,25,26). Considering the lack of significant heterogeneity (I 2 =0.0%, p=0.876), we conducted the synthesized analysis of the four studies using a randomeffects model.…”
Section: Synthesized Analysismentioning
confidence: 99%
“…One of these was excluded because they included other diseases [31]. Thus, nine articles met the inclusion criteria [3,[10][11][12][13][14][15][16][17] (Table 1, Figure 1). One report contained data on two different groups [12], so we analyzed these studies independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Studies on NLR, PLR, and MPV in SLE patients compared to healthy controls, on the relationship between NLR, PLR, and MPV levels and SLE activity, and on the association of NLR with renal involvement in SLE have reported controversial results [3,[10][11][12][13][14][15][16][17]. This may be because of the small sample sizes, low statistical power, and/or the presence of clinical heterogeneity.…”
Section: Introductionmentioning
confidence: 99%